2015
DOI: 10.1007/s00213-015-3876-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased percentages of regulatory T cells are associated with inflammatory and neuroendocrine responses to acute psychological stress and poorer health status in older men and women

Abstract: Rationale The percentage of regulatory T cells (T Regs )-a subtype of T lymphocyte that suppresses the immune response-appears to be reduced in a number of stress-related diseases. The role of the T Reg in stress-disease pathways has not yet been investigated. Objectives The aim of the study was to investigate the association between biological responsivity to acute psychosocial stress and the percentage of T Regs in healthy older adults. The secondary purpose was to measure the associations between T Reg perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Our finding of increased T reg levels in MDD differs from a number of studies that have reported reduced T reg counts in depressed populations (Grosse et al, 2016b; Li et al, 2010). In contrast, our results are consistent with data from a study of elderly subjects that reported that an elevated percentage of T reg cells was associated with worse physical and mental health status, as well as higher levels of depressive symptomatology (Ronaldson et al, 2016). Our finding also is potentially consistent with several preclinical studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of increased T reg levels in MDD differs from a number of studies that have reported reduced T reg counts in depressed populations (Grosse et al, 2016b; Li et al, 2010). In contrast, our results are consistent with data from a study of elderly subjects that reported that an elevated percentage of T reg cells was associated with worse physical and mental health status, as well as higher levels of depressive symptomatology (Ronaldson et al, 2016). Our finding also is potentially consistent with several preclinical studies.…”
Section: Discussionsupporting
confidence: 92%
“…It is conceivable that an upregulation of T reg cell numbers occurs as a compensatory response to high levels of inflammation, leading to a subsequent decrease in CRP concentrations. Irrespective of the mechanism involved, the inverse association between CRP and Treg counts is consistent with a recent study reporting an inverse correlation between IL-6 responses to acute psychophysiological stress and Treg cell counts in the Whitehall II cohort (Ronaldson et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
“…In a cohort of healthy elderly people, the percentage of Tregs was associated with lower physical and mental health and increased depression symptoms. Furthermore, in the same cohort, a greater number of Tregs was associated with a blunted cortisol response and a higher IL-6 response to an acute stressor, which was independent of confounders, such as BMI and smoking (73). Interestingly, blunted cortisol responses and increased IL-6 responses have been observed in ELA (30,74).…”
Section: Discussionmentioning
confidence: 60%
“…Seemingly contrary to the above-mentioned findings, recent studies investigating T-cell and monocytic inflammatory systems in bipolar and schizophrenia patients reported an elevated presence of T-reg cells in association with a monocytic inflammatory signature ( Drexhage et al, 2011a , 2011b ). Additionally, Ronaldson et al (2015) also reported an elevated T-reg cell presence in association with blunted cortisol and increased IL-6 levels in a healthy cohort of volunteers following acute stress. The elevated T-reg cell presence was also found to be correlated with worse physical and mental health status and higher levels of depressive symptomology ( Ronaldson et al, 2015 ).…”
Section: Adaptive Immune System Activation In Depressionmentioning
confidence: 76%